(untitled) - Van Emden, Helmut Fritz (Cambridge, UK,New York, 2004)
As ravagers of crops and carriers of diseases affecting plants, humans and animals, insects present a challenge to a growing human population. In Pest and Vector Control, H.F. van Emden and Mike Service describe the available options for meeting this challenge, discussing their relative advantages, disadvantages and future potential. Methods such as chemical and biological control, host tolerance and resistance are discussed, intergrating--often for the first time--information and experience from the agricultural and medical/veterinary fields. Chemical control is seen as a major component of insect control, both now and in the future, but this is balanced with an extensive account of associated problems, especially the development of pesticide-tolerant populations. The authors are leading authorities in their respective fields and two of the best known entomologists of their generation
Keywords: Pests,Pests,Vector control,Pesticides,Sâu bệnh,Sâu bệnh,Thuốc trừ sâu bệnh; Control,Biological control,Environmental aspects,Kiểm soát,Kiểm soát sinh học,Khía cạnh môi trường